TP1.2.5Colonoscopic Surveillance Versus Surgical Resection After Polypectomy for Colorectal Polyp Cancers: Are We Overtreating Malignant Colorectal Polyps?. (28th October 2021) - Jethwa, Kishan; Pal, Atanu
Abstract: Aims: Colorectal polyp cancers are increasingly detected in the era of screening. This raises the dilemma regarding management by colonoscopic surveillance or surgical segmental resection. The evidence base remains relatively limited and guidelines are still evolving to balance the risk of overtreatment and unnecessary surgical resection or undertreatment and cancer recurrence. In this study we investigate the management of polyp cancers in our centre. Methods: This single centre retrospective study in a university teaching hospital included all patients with malignant colorectal polyps found endoscopically and over a 15-month period. All patients were discussed at the colorectal MDT. The threshold for incomplete endoscopic excision was 1mm. Data from endoscopy reports, histopathology reports and operation notes was collected to determine rate of surgical resection and of residual disease. Results: 70 patients with colorectal polyps, classified as at least high-grade dysplasia, were included. 22/70 polyp cancers (31%) patients had surgical resection. Residual adenocarcinoma was identified in 1/22 (4%) and one further patient had lymph node metastases. Two individual patients developed post-operative ileus and pancreatitis resulting from surgery. Conclusions: Of those patients undergoing surgical resection only 8% patients had malignancy in the postoperative specimen, raising the possibility of overtreatment under current guidelines. This highlights a need to update clinical guidelines to avoid overtreatment without compromising oncological outcomes.